Notes on Dominating Points and Large Deviations (Resenhas do Instituto de Matemática e Estatística da Universidade de São Paulo, 2014)
In these notes ( which supplement my SINAPE lecture) I will survey some early and some current results and applications of the dominating point construction in large deviation theory.